Firm-Specific Responsiveness to Input Price Changes and the Incremental Information in Current Cost Income. - Hopwood, William; Schaefer, Thomas (The Accounting Review, 1989)
Abstract ABSTRACT: Using secure, return cross-sectional association tests, empirical studies to date have yet to show significant Incremental Information In total current cost Income (Including all holding gains) beyond that provided by historical cost Income. The theoretical work of Revsine [1973] and others, however, Indicates that positive unexpected holding gain Information may be good news for some firms but not for others depending on the firms' ability to respond to cost Increases. Therefore, if firms differ in their responses to cost changes, cross-sectional studies may be unable to detect an Incremental Informational effect for total current cost Income. The present study provides evidence which supports the existence of such differential responses across firms. A sample of firms reporting SFAS No. 33 data is partitioned based upon past associations of operating Income with input cost changes. This association provides an empirical measure of firms' relative abilities to adjust operating flows in response to input cost changes. Statistical tests Indicate that such a partition yields significant differences in how equity returns and current cost Income are associated.